2008
DOI: 10.1002/adfm.200800167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu2PO4OH Hierarchical Superstructures with Photocatalytic Activity in Visible Light

Abstract: Using a wet‐chemical method and without any surfactants or templates, various 3D hierarchical superstructures of Cu2PO4OH were synthesized by simply adjusting the pH. The resulting hierarchical superstructures were characterized using X‐ray diffraction (XRD), field‐emission scanning electron microscopy (FESEM), high resolution‐TEM (HRTEM), Fourier transform infrared spectroscopy (FTIR), Raman, and UV–Vis spectroscopy. With an increase in pH from 2.5 to 7.0, the morphology of Cu2PO4OH varied from microrods to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(58 citation statements)
references
References 27 publications
2
54
0
1
Order By: Relevance
“…When the urea concentration was low, the amorphous nanoparticles (step (i)) slowly nucleated. In the subsequent process, the OH − ions were selectively adsorbed on the hydrophilic surfaces of the particles (step (ii)), which resulted in the formation of the nanorods through the anisotropic growth (step (iii)) [28,29]. Similar rod-like brookite TiO 2 nanoparticles were previously observed by Kominami et al [16].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…When the urea concentration was low, the amorphous nanoparticles (step (i)) slowly nucleated. In the subsequent process, the OH − ions were selectively adsorbed on the hydrophilic surfaces of the particles (step (ii)), which resulted in the formation of the nanorods through the anisotropic growth (step (iii)) [28,29]. Similar rod-like brookite TiO 2 nanoparticles were previously observed by Kominami et al [16].…”
Section: Resultsmentioning
confidence: 72%
“…The surfaceadsorbed OH − and NH 4 + ions linked through the self-assembly of electrostatic attractions and repulsions, thereby producing the flower-like clusters, in Fig. 4 [29][30][31]. A previous report showed that the increased concentration of the Na + and OH − ions strengthened the assembly of the nanoparticles during the formation of the brookite TiO 2 flowers.…”
Section: Resultsmentioning
confidence: 92%
“…The experiments were carried out in an ultra-high vacuum system with a base pressure of about 6×10 −10 Pa. The XPS spectra were recorded in normal emission [10][11][12][38][39][40]. For the XPS analyses, the CasaXPS 2.3.14 software (Shirley background type) was used.…”
Section: Setup Of Xpsmentioning
confidence: 99%
“…Cho et al reported the synthesis of Cu 2 (OH)PO 4 with various 3D hierarchical superstructures by using a wet-chemical method. They demonstrated firstly the useful photocatalytic activity of these complex structures in the degradation of methylene blue dye under visible light irradiation [31]. In this paper, we investigated the wet hydrogen peroxide catalytic oxidation of an azo dye (Direct Brown 2) using Cu 2 (OH)PO 4 .…”
Section: Introductionmentioning
confidence: 99%